Behind male Saudi nursing students’ mental health facade: a husserlian phenomenological approach - Ejercito Mangawa Balay-odao; Nahed Alquwez; Abdulellah Al Thobaity; Khalaf Al Otaibi; Yousef Ali Abdulrahman Alsakran; Jonas Preposi Cruz (BMC Nursing, 2021)
Abstract Background Every person has a persona (or mask) which is the façade that every person shows to the world. Thus, males use façade to reveal or conceal their true feelings and emotions. Also, the male uses mental health façade to protect themselves from prejudice and judgment. Thus, the study aimed to explore the experiences of male Saudi nursing students of mental health. Method Husserl’s descriptive phenomenology was used as a guiding lens to explore. Eleven participants were involved in the study by using the referral sampling technique. An unstructured interview was performed to gather information from the participants. The seven steps of the descriptive Colaizzi process were followed to investigate and examine the obtained data. The credibility, dependability, confirmability, transferability, and reflexivity criteria were observed to ensure the rigor of the study. Results The findings have two major themes. The first theme is the unadulterated smile that describes optimism in the family and mutual guarantee. The second theme is the orchestrated smile, which describes avoiding diverting burdens, social responsibility, protection of self, and reputation. Conclusions The findings document that the mental health façade of male Saudi nursing students is associated with the expectation of family optimism, mutual guarantee, the expectation of society, and self-protection.